Zoonotic infections among veterinarians in Turkey: Crimean-Congo hemorrhagic fever and beyond - (:unkn) unknown (ELSEVIER SCI LTD, 2006)
Objectives: We aimed to determine the seroprevalence of Crimean-Congo hemorrhagic fever (CCHF) virus, Brucella spp, and Coxiella burnetii among veterinarians in a highly endemic and a non-endemic region for these infections in Turkey. Methods: The antibody levels against these three infections were surveyed. Eighty-three veterinarians were included from two distinct geographic regions. Results: CCHF IgG positivity (3% vs. 0%) and Brucella agglutination titer of >= 1/160 (33% vs. 5%) were more common in the endemic region, whereas the rates of Coxiella burnetii antibodies were similar (7% and 8%). A history of tick bite was significantly more common in the endemic region (35% vs. 12%, p = 0.011). A multivariate analysis was performed among the veterinarians living in the endemic area, and percutaneous injuries were found to be associated with Brucella infection (OR 1.8, Cl 1.09-3, p = 0.022). Conclusions: Veterinarians should protect themselves against tick bites, and should use masks to prevent transmission by inhalation of zoonotic infections in endemic countries. (c) 2006 International Society for Infectious Diseases. Published by Elsevier Ltd. All rights reserved.
Keywords: veterinarians; antibody; Crimean-Congo hemorrhagic fever virus; Brucella spp; Coxiella burnetii; RISK-FACTORS; SEROPREVALENCE; ANTIBODIES; OUTBREAK; PEOPLE